Stability Analysis and Optimization of Wind Energy Conversion System Using Extremum Seeking Output Feedback Controller for Dynamic Wind Speed Variations - B.Hemanth Kumar, M.; Saravanan, B. (International Journal of Engineering and Technology, 2018)
Stability of power systems is an important aspect for interconnecting different renewable energy sources into the existing electrical network. The concern over environmental effects due to conventional power plant made the researchers to implement many solutions for introducing renewable energy due to their intermittent nature. When the wind energy conversion system is introduced into the grid thereâ€™s need of voltage and frequency control for maintaining reactive power demand and also many issues from the consumer end and also it must satisfy the grid standards. As the wind is dynamic in nature there are issues like stability, load imbalance, power quality and other issues. In this paper, a non-linear feedback controller is introduced based on field-oriented control (FOC) approach and simulated in MATLAB environment. The designed controller is tested for wind data for examining the stability and power coefficient for the wind turbine. This controller also achieves fast transient response for rapid changes in the wind profile.Â Â